Small fiber neuropathy in Sjögren syndrome: Comparison with other small fiber neuropathies. Issue 4 (15th February 2020) - Descamps, Elise; Henry, Julien; Labeyrie, Céline; Adams, David; Ghaidaa, Adebs Nasser; Vandendries, Christophe; Adam, Clovis; Aiello, David; Mariette, Xavier; Seror, Raphaèle
Abstract: Introduction: We compared histological and clinical profiles of primary Sjögren syndrome (pSS) small fiber neuropathy (SFN; pSS‐SFN) with idiopathic SFN (i‐SFN) and hereditary transthyretin amyloidosis SFN (hATTR‐SFN) and described the evolution of pSS‐SFN. Methods: All patients with pSS‐SFN, i‐SFN, and hATTR‐SFN confirmed by reduced intraepidermal nerve fiber density on skin biopsy were retrospectively included, and their characteristics were compared. To analyze prognosis of pSS‐SFN, patients prospectively underwent a second evaluation. Results: Fifteen pSS‐SFN, 17 hATTR‐SFN, and 11 i‐SFN were included. Time to diagnosis SFN was longer in pSS‐SFN and i‐SFN than in hATTR‐SFN. Painful and non–length‐dependent patterns were more frequent in pSS‐SFN than in hATTR‐SFN. Twelve (80%) patients with pSS‐SFN had a non–length‐dependent pattern. Ten patients with pSS were reassessed after 3.1 years (1.7–4.7); none developed large fiber neuropathy linked to pSS. Discussion: Primary Sjögren syndrome SFN is characterized by a more frequent non–length‐dependent pattern compared with i‐SFN and hATTR‐SFN. Primary Sjögren syndrome SFN did not evolve through large fiber neuropathy.